6n+8(n+3)=-2(2+2n)-8

Simple and best practice solution for 6n+8(n+3)=-2(2+2n)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n+8(n+3)=-2(2+2n)-8 equation:


Simplifying
6n + 8(n + 3) = -2(2 + 2n) + -8

Reorder the terms:
6n + 8(3 + n) = -2(2 + 2n) + -8
6n + (3 * 8 + n * 8) = -2(2 + 2n) + -8
6n + (24 + 8n) = -2(2 + 2n) + -8

Reorder the terms:
24 + 6n + 8n = -2(2 + 2n) + -8

Combine like terms: 6n + 8n = 14n
24 + 14n = -2(2 + 2n) + -8
24 + 14n = (2 * -2 + 2n * -2) + -8
24 + 14n = (-4 + -4n) + -8

Reorder the terms:
24 + 14n = -4 + -8 + -4n

Combine like terms: -4 + -8 = -12
24 + 14n = -12 + -4n

Solving
24 + 14n = -12 + -4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4n' to each side of the equation.
24 + 14n + 4n = -12 + -4n + 4n

Combine like terms: 14n + 4n = 18n
24 + 18n = -12 + -4n + 4n

Combine like terms: -4n + 4n = 0
24 + 18n = -12 + 0
24 + 18n = -12

Add '-24' to each side of the equation.
24 + -24 + 18n = -12 + -24

Combine like terms: 24 + -24 = 0
0 + 18n = -12 + -24
18n = -12 + -24

Combine like terms: -12 + -24 = -36
18n = -36

Divide each side by '18'.
n = -2

Simplifying
n = -2

See similar equations:

| 5=6w-9w-1 | | 16+3x+38=96 | | 16+3x+38+96=180 | | 7+4(1-4a)=-12+7a | | 5=6w-8w-1 | | x+0.1x=.017 | | 16x+3x+38=96 | | X^2+y^2+6X+2y+6=o | | -25=-10+1p | | 2p-5+7p=19+5p | | 2+5y=-3 | | 5y+3=3y-1 | | -5x+7y=1 | | 2r+2(5r+6)=-6+6r | | (4x-6)(8x+2)=0 | | (2x+3)(3x^2+2x-5)= | | 12y+180+6x=180 | | 138=-3(6n+2) | | x+3=152 | | 9s+3=67 | | 9x+7y=100 | | 0=10x+x^2-144 | | 5(-g-10)=6-13g | | 5+5n+5n=-15 | | (X+43)+(2x-73)=180 | | (7q-7)+(5q-9)= | | 6x+1=3(2x+1)-x+8 | | x+-5y=-3 | | 10x^2-45x-25=0 | | X+11=5x-2 | | -64-(4x-14)=15 | | b+10=96 |

Equations solver categories